2017
DOI: 10.1074/jbc.m117.804716
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase A–induced internalization of Slack channels from the neuronal membrane occurs by adaptor protein-2/clathrin–mediated endocytosis

Abstract: The sodium-activated potassium (K) channel Kcnt1 (Slack) is abundantly expressed in nociceptor (pain-sensing) neurons of the dorsal root ganglion (DRG), where they transmit the large outward conductance and arbitrate membrane excitability. Slack channel expression at the DRG membrane is necessary for their characteristic firing accommodation during maintained stimulation, and reduced membrane channel density causes hyperexcitability. We have previously shown that in a pro-inflammatory state, a decrease in memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…S3A). We expected the decrease in surface Slack K Na channels to result in repetitive firing (14,15); however, the observed severely stunted APs suggested that Magi-1 deficiency was also affecting sodium channel functioning.…”
Section: K Na Channel Expression Is Affected By the Pdz Binding Motifmentioning
confidence: 95%
See 4 more Smart Citations
“…S3A). We expected the decrease in surface Slack K Na channels to result in repetitive firing (14,15); however, the observed severely stunted APs suggested that Magi-1 deficiency was also affecting sodium channel functioning.…”
Section: K Na Channel Expression Is Affected By the Pdz Binding Motifmentioning
confidence: 95%
“…For electrophysiological experiments, DRG neurons were cotransfected with the GFP-containing plasmid pTRACER and siRNA duplexes for positive indication of transfection. Imunofluorescence procedures on cultured neurons were performed as previously described (15). The investigator was blinded to the transfection condition.…”
Section: Drg Neuron Small Interfering Rna Transfectionmentioning
confidence: 99%
See 3 more Smart Citations